Description of five new species of American Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) - Vlasak, Josef; Santos-Silva, Antonio (Zootaxa, 2021)
Five new species of Acanthocinini are described: Onalcidion maculatum, from Costa Rica; Lethes x-notatus, from Costa Rica; Leptostylus indistinctus, from Costa Rica; Leptostylus guianensis, from French Guiana; and Trichotithonus thomasvlasaki, from Ecuador.